“After the floods, he says he is an environmentalist”: Understanding blended roles and organizational boundaries in decision-making under uncertainty during unprecedented floods in Wayanad, India - Koshy, Mrudhula (Frontiers in Sustainable Cities, 2022)
An increase in unprecedented environmental crises as a result of climate change and human influence has amplified calls for recognizing the complexity of decision-making under uncertainty (DMUU). How decision-makers act in institutional settings under uncertainty has, however, received limited attention in decision-making in planning practice. This article investigates DMUU in the context of Wayanad, a peri urban hill district in Kerala, India through two decision settings; the response to unprecedented heavy monsoon floods in 2018 and 2019 as a case of short-term uncertainty, and policy and plan making regarding quarrying in ecologically sensitive areas as a case of long-term uncertainty. Through empirical findings from semi-structured interviews of 58 decision-makers from state and non-state actors, the article discusses individual and collective actions made before, during and after the floods by combining insights on DMUU from spatial planning and governance literature underpinned by spatial-temporal and political ecology narratives. The article argues that factors such as community resourcefulness and decentralized governance appeared to facilitate effective decision-making under short-term uncertainty. However, the same factors did not have an intrinsic influence on decision-making under long-term uncertainty with current ways of decision-making regarding quarrying in ecologically sensitive areas likely obstructing sustainable long-term planning and land use transformation in Wayanad. The article concludes with recommendations for potential improvements in decision-making under long-term uncertainty in contexts with weak institutional mechanisms, chronic vulnerabilities and resource scarcity, through structural organizational change, cross-sectoral decision-making arenas, and decision-making frameworks that foregrounds heuristic, flexible, incremental, and cumulative actions across scales over time.